Peningkatan Sikap Kedisiplinan Pada Pembelajaran PKN Menggunakan Model Paradigma Pedagogi Reflektif Bagi Siswa Kelas III dI SD Negeri Koli - Sufri Saleh (Jurnal Ilmiah Wahana Pendidikan, 2023)
One of the learning objectives in Civics is to form an attitude of discipline. So, through the use of learning models in Civics subjects it is expected to develop the character of students. The purposes of this research were 1) to describe and find out the implementation of learning using the reflective pedagogical paradigm model (PPR) in Civics learning for Grade III students at Koli Public Elementary School in an effort to improve student discipline and 2) to improve and find out the increase in disciplinary attitudes in Civics learning for class students III SD Negeri Koli uses the PPR learning model. The research conducted is Classroom Action Research (CAR) to improve students' disciplinary attitudes towards the rules that apply in society. The research was conducted for 2 cycles each cycle through the stages of planning, action, observation and reflection. The data collection technique used as a guide is an attitude scale questionnaire. The results of the research conducted on the use of the reflective pedagogical paradigm learning model in Civics teaching and learning activities in class III SD Negeri Koli can improve student discipline. The increase in students' disciplinary attitudes can be seen from the results of the average disciplinary attitude obtained in the initial conditions of 64.675, in cycle 1 of 77.825, and cycle 2 of 82.85. The percentage of students who have minimal discipline at the initial condition is 52.50%, cycle 1 is 95%, and cycle 2 is 95%.